The pinewood nematode and pine wilt disease: a serious forest protection issue - Mota, Manuel (2012)
Bursaphelenchus xylophilus, the pinewood nematode (PWN), and the causal agent of pine wilt disease (PWD), was detected for the first time in 1999, in Europe, in Portugal. The PWN has been detected in new forest areas in the center of the country, in 2008, despite efforts developed by the national forestry and quarantine authorities to control the nematode and its insect vector (Monochamus galloprovincialis). The nematode has also recently been reported to be present from Spain. Circulation of non-treated wood and wood products may explain the spread of the nematode. Control strategies have been focused on the vector by using chemical traps, by cutting down symptomatic trees, heat-treatment of lumber, and monitoring of main roads and ports through which lumber and wood products are transported, by the Portuguese authorities. The nematode constitutes a threat to the rest of Europe, if proper measures are not taken European governments. Study topics on this issue include nematode and insect bioecology, pathogenicity, use of molecular biology in diagnostics and detection, histopathology, etc. Many gaps in the knowledge of this complex biological system persist. The involvement of bacteria, associated with the PWN in causing pine wilt, has been claimed. New quick detection methods and the understanding of the nematode population dynamics are being developed. Nematode genomics may provide some insight to better understand the pathogenic effects caused inside the plant. Pathogenicity testing of susceptible pine species is imperative. A review of the progress is hereby presented.